Manajemen Kepemimpinan dalam Perspektif Al- Qur'an - Septian Khoirul Umam (Universitas Islam Negeri Walisongo, 2023)
Every organization definitely needs a leader to condition an activity to run effectively. An organization looks good when a leader brings positive things and conversely an organization looks bad when a leader brings negative things. The aim of this research is to describe leadership management from the perspective of the Koran. In this article the researcher uses the literature method, namely collecting several references related to titles such as books, journals and articles. Researchers also use a qualitative descriptive approach, namely a research approach that refers to aspects of opinion or ways of social understanding of society in general. The results of the research reveal that there are many verses in the Koran that discuss leadership management, so before the rise of leadership in the world of education or an Islamic organization, it was already discussed in the Koran, which used words such as: caliph, imam, and ulil amri. in accordance with the concept of leadership in Islam. Even in discussing Islamic education management, it will still be related to POAC (planning, organizing, actuating, and controlling) which is a management function.